Protein kinase C enhances human sodium channel hNav1.7 resurgent currents via a serine residue in the domain III–IV linker. Issue 21 (19th September 2014) - Tan, Zhi-Yong; Priest, Birgit T.; Krajewski, Jeffrey L.; Knopp, Kelly L.; Nisenbaum, Eric S.; Cummins, Theodore R.
Abstract : Resurgent sodium currents likely play a role in modulating neuronal excitability. Here we studied whether protein kinase C (PKC) activation can increase resurgent currents produced by the human sodium channel hNav1.7. We found that a PKC agonist significantly enhanced hNav1.7‐mediated resurgent currents and this was prevented by PKC antagonists. The enhancing effects were replicated by two phosphorylation‐mimicking mutations and were prevented by a phosphorylation‐deficient mutation at a conserved PKC phosphorylation site (Serine 1479). Our results suggest that PKC can increase sodium resurgent currents through phosphorylation of a conserved Serine residue located in the domain III–IV linker of sodium channels. Abstract : PKC activation increased resurgent currents produced by hNav1.7. Phosphorylation‐mimicking mutations at S1479 increased resurgent currents. Phosphorylation‐deficient mutation prevented increasing effects of PKC. These data suggest PKC increases resurgent currents through S1479 phosphorylation.